Resistance to the motherhood mandate: Discourses on non-motherhood among women aged 25 to 45 from middle and upper strata in Metropolitan Lima who have chosen not to have children - Altamirano Camacho, Karol Josefina (2024)
This article examines the complex dynamics of non-motherhood in contemporary Peruvian society, focusing on middle and upper-class women in Metropolitan Lima. By  employing a qualitative methodology centered on narratives, the study explores the meanings attributed to motherhood and non-motherhood, challenging concepts such as "maternal instinct." Autonomy emerges as a right and diverse reasons for choosing not to become a mother are revealed. Moreover, the study addresses stigma, social pressure, and moral violence, highlighting strategies of resistance against the maternal mandate and the construction of new female identities. The article advocates for inclusive dialogue regarding the life choices of these women.